Factual Text Genre: Analysis of the Ability of High School Teachers in Developing Learning Tools - Safi’i, Imam; Tarmini, Wini; Ilyas, Hamzah Puadi (Jurnal Pendidikan Progresif, 2020)
Factual Text Genre: Analysis of the Ability of High School Teachers in Developing Learning Tools. Objective: This study aims to describe the ability of Indonesian language teachers in Banten Provision in designing factual text genre. Method: The method was content analysis. The research sample was taken purposively through the XII grade. Indonesian Language Lesson Plan Module compiled. Data collection and analysis were done by measuring the relevance of data categorization in terms of genre pedagogical, genre scientific, and the completeness of the evaluation instrument. Findings: The average ability of teachers in describing learning with genre pedagogical approach was 67%; the ability of teachers in describing genre scientific methods was 83%; the ability of teachers in making assessment instruments based on the genre of text was 50%. Conclusion: Teachers’ competence in designing textual genre-based learning was not optimal. The results of this study can be utilized as an assessment of the effectiveness of the implementation of Indonesian language learning based on the text genre.Keywords: factual text genre, high school teacher, content analysisDOI: 10.23960/jpp.v10.i2.202008